Postural balance in the elderly with and without Type 2 Diabetes Mellitus: A comparative analysis (Research, Society and Development, 2021)
The present study aimed to investigate the postural balance of elderly people with and without Type 2 Diabetes Mellitus (DM2) and to verify the associated clinical characteristics. It is an observational, analytical and cross-sectional study; 233 elderly people (60 years or older) were evaluated, 147 with a diagnosis of DM2 (G1) and 86 without DM2 (G2). Postural balance was assessed using the Mini - The Balance Evaluation Systems Test (MiniBESTest). The associations between the total scores of G1 and G2 were verified using the Mann-Whitney tests and the Chi-square test, α = 0.05. After inferential analysis, significance was observed between variables in groups G1 and G2: BMI (p = 0.048), number of medications (p = 0.001), motor TUGt (p = 0.015), FPP (p